2023
DOI: 10.3390/molecules28227568
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods Based on the Mass Balance Approach for Purity Evaluation of Tetracycline Hydrochloride

Sunyoung Lee,
Song-Yee Baek,
Ha-Jeong Kwon
et al.

Abstract: Analytical methods based on the mass balance approach were developed for the purity evaluation of tetracycline hydrochloride, a representative salt compound used in pure veterinary drug analysis. The purity assignment method was used to quantify individual classes of impurities via independent analytical techniques. The mass fraction of the free base or salt form contained in a high-purity organic compound with a hydrochloride salt can be determined. The chloride content by ion chromatography-conductivity dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Tu et al [24] comprehensively summarized the types of domestic and international certified reference materials for neonicotinoid pesticides, along with sample preparation and determination techniques. Lee et al [25] accurately evaluated the purity of the free base and salt forms of tetracycline hydrochloride using the mass balance method, with results traceable to SI units.…”
Section: Introductionmentioning
confidence: 99%
“…Tu et al [24] comprehensively summarized the types of domestic and international certified reference materials for neonicotinoid pesticides, along with sample preparation and determination techniques. Lee et al [25] accurately evaluated the purity of the free base and salt forms of tetracycline hydrochloride using the mass balance method, with results traceable to SI units.…”
Section: Introductionmentioning
confidence: 99%
“…, organic impurities, moisture, and inorganic substances) that may be present in the organic material and to make deductions for them. 1 However, many impurities are difficult to characterise, purchase or synthesize. This requires extensive identification studies, which may not be successful if some of the major impurities cannot be identified or their reference materials cannot be obtained.…”
Section: Introductionmentioning
confidence: 99%